2022
DOI: 10.31083/j.fbl2709278
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tangning Ziyabitusi on Gut Microbiota and T lymphocyte Subsets in Impaired Glucose Regulation Rats

Abstract: Background: Impaired glucose regulation (IGR) represents the prediabetic state and is associated with gut microbiota (GM) dysbiosis and chronic inflammation. Tangning Ziyabitusi Tablet (TZT) is a Chinese Uyghur herbal medicine with preventative and therapeutic effects on diabetes, but its hypoglycemic mechanisms are unclear. Methods: Thirty-six male Wistar rats were divided into the normal diet (ND) and IGR groups. The IGR group was given a high-fat diet (HFD). After the IGR model establishment, the ND group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Norank_f__Muribaculaceae improve glucose tolerance and insulin resistance in diabetic mice, which may be dependent on their regulation of the SCFA level [77,78]. In this study, consistent with previous studies [79][80][81], the relative abundance of these negatively correlated bacteria significantly decreased in diabetic mice (Table 3) but increased significantly after TFs or metformin intervention (Table 3). These changes in bacteria both positively and negatively correlated with diabetes suggested that TFs could reshape the structure of the gut microbiome, and this may be a strategy to improve diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…Norank_f__Muribaculaceae improve glucose tolerance and insulin resistance in diabetic mice, which may be dependent on their regulation of the SCFA level [77,78]. In this study, consistent with previous studies [79][80][81], the relative abundance of these negatively correlated bacteria significantly decreased in diabetic mice (Table 3) but increased significantly after TFs or metformin intervention (Table 3). These changes in bacteria both positively and negatively correlated with diabetes suggested that TFs could reshape the structure of the gut microbiome, and this may be a strategy to improve diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…Lactobacillus as beneficial bacteria can alleviate inflammation and plays a positive role in antioxidant and glucose-lowering effects, 28 whereas Adlercreutzia abundance is associated with obesity and insulin resistance in rodents. 29 LEfSe analysis showed that Odoribacter, Ruminiclostridium, and Clostridium_sensu_stricto_1 were more abundant in the GAMG group. These three key genera can produce SCFAs.…”
Section: Discussionmentioning
confidence: 94%
“…Sucralose increased the Adlercreutzia abundance, which was positively correlated with FBG and the AUC of OGTT, suggesting that Adlercreutzia may be related to the aberrant glycemic response. 29 Additionally, Muribaculaceae_norank, increased in the aspartame group, was negatively correlated with GLP-1 and the gene expression of PYY receptor and GPR43. Aspartame also reduced the butyric acid level.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations